Distributive fairness in an intercultural ultimatum game - Sebastian Georg; Werner Güth; Gari Walkowitz; Torsten Weiland (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
Does geographic or (perceived) social distance between subjects significantly affect proposer and responder behavior in ultimatum bargaining? To answer this question, subjects once play an ultimatum game with three players (proposer, responder, and dummy player) and asymmetric information (only the proposer knows what can be distributed). Treatments differ in their geographical scope in that they involve either one or three subject pools which, in the latter case, structurally differ in their between-subject pool heterogeneity. Observed choice behavior corroborates several stylized facts of this class of ultimatum games which are primarily explained by strategic play and otherregarding preferences. While the extent of self-interested allocation behavior in proposers significantly varies across sites, neither proposers nor responders meaningfully condition their choices on their co-players provenance or affiliation. Altogether, we do not discern articulate discriminative behavior based on geographic or social distance.
Keywords: C70; C91; D63; 330; Equity; fairness; social preferences; ultimatum bargaining; redistribution; cross-national experiment; Verhandlungstheorie; Multikulturell; Gerechtigkeit; Test